2015
DOI: 10.1007/s00894-015-2766-2
|View full text |Cite
|
Sign up to set email alerts
|

The stability and decomposition mechanism of the catenated nitrogen compounds

Abstract: Through theoretical calculation and experimental data, the decomposition mechanism of the N,N'-azo azole poly-nitrogen compounds were obtained. The compounds with the decomposition caused by the rupture of the -N-N=N-N- bridge are more stable than the ones with the ring-opening decomposition mechanisms. The catenated -N-N=N-N- bridge can strengthen the stability of the nitrogen chain. Preventing the hybridization change of the N atom where the ring-opening reaction occurs is essential for the nitrogen chain el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Nearly all available computational results on the thermal decomposition of azobis triazoles and tetrazoles were obtained at the DFT level of theory with the B3LYP functional. More specifically, Zhao et al studied the thermal decomposition of 1 , 2a (Chart ) and several of their isomers. The authors found that the catenation of the long nitrogen-chains facilitates the decomposition via the ring-opening and subsequent elimination of the molecular nitrogen. For 1 and 2a , the activation barriers of the rate-determining N 2 elimination steps were predicted to be 34.6 and 27.5 kcal mol –1 , respectively .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nearly all available computational results on the thermal decomposition of azobis triazoles and tetrazoles were obtained at the DFT level of theory with the B3LYP functional. More specifically, Zhao et al studied the thermal decomposition of 1 , 2a (Chart ) and several of their isomers. The authors found that the catenation of the long nitrogen-chains facilitates the decomposition via the ring-opening and subsequent elimination of the molecular nitrogen. For 1 and 2a , the activation barriers of the rate-determining N 2 elimination steps were predicted to be 34.6 and 27.5 kcal mol –1 , respectively .…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the catenation of the long nitrogen-chains facilitates the decomposition via the ring-opening and subsequent elimination of the molecular nitrogen. For 1 and 2a , the activation barriers of the rate-determining N 2 elimination steps were predicted to be 34.6 and 27.5 kcal mol –1 , respectively . The same decomposition mechanism was proposed for 4 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations